STRUCTURAL DAMAGE IDENTIFICATION WITH GENERALIZED FLEXIBILITY AND ADDED MASSES - ZHOU WeiDong; YANG QiuWei; ZHAO Wei (Jixie qiangdu)
In this study,a method is proposed to identify structural damages by the change of structural generalized flexibility. By adding known masses to the physical structure,measuring the lower modes of the mass-modified structure,and then using these new data as well as the original test information,structural damages can be detected using the generalized flexibility perturbation technique. The effectiveness of the proposed method is illustrated using simulated data on a plane truss structure. The results show that the proposed method can identify structural damages accurately only using the first modal parameters. The presented scheme may be useful for damage identification of large-scale structures.